1995
DOI: 10.1093/jnci/87.13.997
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Angiogenesis as a Prognostic Assay for Invasive Ductal Breast Carcinoma

Abstract: Microvessel count showed much variation among different regions of each tumor. It did not predict metastasis-free survival or overall survival. Nodal status was the most powerful criterion to stratify these patients with invasive ductal carcinoma of the breast into different survival groups. Only ER status, tumor grade, and p53 staining had additional prognostic utility for these patients after they had been stratified by nodal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
2
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(121 citation statements)
references
References 5 publications
6
107
2
6
Order By: Relevance
“…Other studies that did not show an association between MVD and outcome include those by Axelsson et al and several others in which MVD did not predict metastasis-free survival or overall survival in patients with invasive breast carcinoma [21][22][23]. Leedy et al and Rutgers et al also found that MVD was not useful in determining outcome in patients with squamous cell carcinoma of the tongue or cervix, respectively [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…Other studies that did not show an association between MVD and outcome include those by Axelsson et al and several others in which MVD did not predict metastasis-free survival or overall survival in patients with invasive breast carcinoma [21][22][23]. Leedy et al and Rutgers et al also found that MVD was not useful in determining outcome in patients with squamous cell carcinoma of the tongue or cervix, respectively [24,25].…”
Section: Discussionmentioning
confidence: 96%
“…The initial observation of Weidner et al (1991) that high vascular density in the primary tumour may promote metastasis in breast carcinoma was not confirmed in two recent, extensive studies. Axelsson et al (1995) analysed tumour specimens from 220 patients with breast carcinoma and found no correlation between the vascular density of the primary tumour and metastasis-free survival or overall survival. Similarly, Goulding et al (1995) examined specimens from the primary tumour of 165 breast cancer patients and found no correlation between tumour vascularity and incidence of distant metastases or overall survival probability.…”
Section: Discussionmentioning
confidence: 99%
“…i, tumours from younger patients had higher vascuthan those from older patients. However, several een unable to confirm the statistical significance of n (van Hoef et al, 1993;Axelsson et al, 1995;Bossi han and Stein, 1995). A lack of association between prognostic indicators has previously been reported endleton et al, 1996), oral carcinoma (Williams et al, neous melanoma (Busam et al, 1995).…”
Section: Analysis Of Survivalmentioning
confidence: 99%
“…This hypothesis is widely accepted, so that vascularity measured in histological sections using pan-endothelial antibodies is increasingly referred to as 'angiogenesis'. The validity of this hypothesis, however, is questioned by results of several studies that found either no association between vascularity and prognosis (Hall et al, 1992;van Hoef et al, 1993;Axelsson et al, 1995;Busam et al, 1995;Tahan and Stein, 1995;Morphopoulos et al, 1996) or highest vascularity associated with good prognosis (Kainz et al, 1995;Zatterstrom et al, 1995).…”
mentioning
confidence: 99%